Research on the Effects of Lying on Memory: A Scientometric Analysis and a Call for New Studies - Battista, Fabiana; Otgaar, Henry (Frontiers in Psychology, 2022)
Research on the effects of lying and memory is increasingly attracting empirical attention. In the current manuscript, a scientometric analysis was carried out on the mnemonic consequences of lying. This analysis took into account 70 published articles extracted from Scopus and Web of Science databases from 1998 to 2021. A scientometric analysis was conducted in order to visualize the state of art on this line of research (i.e., authors, countries, institutions, journals, and co-citations). Additionally, a keywords’ cluster analysis was executed to investigate the main keywords used in the published papers. Based on the keywords’ cluster analysis, we identified the main aims and critical issues of the reviewed papers. The United States and the Netherlands are the two most productive countries into the effects of lying on memory. The top five authors are mainly from European countries and wrote from 6 to 15 articles. The cluster analysis detected three clusters of keywords. The critical issues of this line of research are mainly related to the generalizability of the achieved findings for real situations, a lack of a direct control of the manipulation adopted, and a need of additional measures. The current analysis provides a comprehensive overview and understanding of existing research on the effects of lying on memory and provides possible future directions of this research domain.